EACVI SIMULATOR-online study: evaluation of transoesophageal echocardiography knowledge and skills of young cardiologists. (24th September 2022) - Pezel, Théo; Coisne, Augustin; Michalski, Błażej; Soliman, Hatem; Ajmone, Nina; Nijveldt, Robin; Stankovic, Ivan; Donal, Erwan; van der Maaten, Joost; Papadopoulos, Constantinos; Edvardsen, Thor; Muraru, Denisa; et al.
Abstract: Aims: To assess the level of transesophageal echocardiography (TOE) knowledge and skills of young cardiologists. Methods and results: A European Association of Cardiovascular Imaging (EACVI) online study using the first fully virtual simulation-based software was conducted in two periods (9–12 December 2021 and 10–13 April 2022). All young cardiologists eligible to participate (<40 years) across the world were invited to participate. After a short survey, each participant completed two tests: a theoretical test to assess TOE knowledge and a practical test using an online TOE simulator to investigate TOE skills. Among 716 young cardiologists from 81 countries, the mean theoretical test score was 56.8 ± 20.9 points, and the mean practical test score was 47.4 ± 7.2 points (/100 points max each), including 18.4 ± 8.7 points for the acquisition test score and 29.0 ± 6.7 points for the anatomy test score (/50 points max each). Acquisition test scores were higher for four-chamber (2.3 ± 1.5 points), two-chamber (2.2 ± 1.4 points) and three-chamber views (2.3 ± 1.4 points) than for other views (all P < 0.001). Prior participation to a TOE simulation-based training session, a higher number of TOE exams performed per week, and EACVI certification for TOE were independently associated with a higher global score (all P < 0.001). Conclusion: Online evaluation of young cardiologists around the world showed a relatively low level of TOE skills and knowledge. Prior participation to a TOE simulation-based training session, a higher number of TOE exams performed per week, and the EACVI certification for TOE were independently associated with a higher global score.